'Might is Right': A study of the Cape Town/Crozets elephant seal oil trade (1832-1869) - Rousset, Thierry Jean-Marie (Department of Historical Studies, 2015)
This thesis is the study of Cape involvement in the elephant seal oil trade on the Prince Edward Islands and Crozet Islands between the years 1832-1869.